Toward National Harmonization: A Dialogue Between Islamic Education and Multiculturalism in Indonesia - Maftuh, Hasan; Saerozi, Muh; Ruwandi, Ruwandi; Zaman, Badrus; Surjanto, Ana Nurkhasanah (Institut Muslim Cendekia, 2026)
This research aimed to examine the synergy between Islamic education and multicultural values as a strategic instrument for achieving national harmonization in Indonesia. Indonesia is a pluralistic nation rich in ethnic, cultural, and religious diversity, yet historically vulnerable to horizontal conflicts. Utilizing a qualitative method with a phenomenological approach, this study explored into the collective experiences of educators and students. Data analysis was grounded based on Talcott Parsons’ Structural Functionalism theory (AGIL) and James A. Banks’ dimensions of multicultural education. The results indicated that the integration of Islamic education and multiculturalism functioned as an ideological framework that shaped and transformed dogmatic worldviews into inclusive-humanist perspectives. Dialogue strategies implemented through religious moderation and a curriculum repositioning that emphasized equality and prejudice reduction serve as the primary keys to mitigating potential conflict. This study concluded that Islamic education played a vital role as a pillar of social integration in preserving Pancasila values amidst global dynamics and the challenges of the millennial era.